2000
DOI: 10.1007/pl00011992
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in the structure of grassland butterfly communities along a gradient of human disturbance: further analysis based on the generalist/specialist concept

Abstract: Kitahara and Fujii, in 1994, analyzed the butterfly communities along a gradient of human disturbance by applying the generalist/specialist concept. Butterfly species were classified into generalist or specialist species based on their voltinism (seasonal time dimension) and potential larval resource breadth (food dimension). The community structure and species composition showed the systematic changes along the gradient. To verify the generality of those trends, we monitored five grassland butterfly communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
54
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 42 publications
7
54
1
1
Order By: Relevance
“…numerous treatments during spring, summer and autumn) might have further lowered the abundance of the remaining butterflies. These findings are supported by other studies that indicate butterfly diversity in general decreases along gradients of increasing human disturbance (Yamamoto, 1977;Ruszczyk & DeAraujo, 1992;Kitahara et al, 2000;Kitahara & Sei, 2001;Schmitt, 2003). (Bink, 1992) for meadow fallow land, forest fallow land and mixed fallow land transects (i.e.…”
Section: Aricia Agestis Coenonympha Arcania Polyommatus Semiargus supporting
confidence: 84%
“…numerous treatments during spring, summer and autumn) might have further lowered the abundance of the remaining butterflies. These findings are supported by other studies that indicate butterfly diversity in general decreases along gradients of increasing human disturbance (Yamamoto, 1977;Ruszczyk & DeAraujo, 1992;Kitahara et al, 2000;Kitahara & Sei, 2001;Schmitt, 2003). (Bink, 1992) for meadow fallow land, forest fallow land and mixed fallow land transects (i.e.…”
Section: Aricia Agestis Coenonympha Arcania Polyommatus Semiargus supporting
confidence: 84%
“…However, there is a lot of anxiety on the status of the earth's biodiversity [4] and from this observation, biodiversity is being rapidly depleted resulting in a threat to the continued support that nature make available for human existence and development [5]. Several animal species could tolerate only a limited level of human disturbances in their natural environments [6]. This is of special significance to Nigerian landscapes where human impact on land use for several hundreds of years changed the great majority of natural habitats [7].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, diversity patterns depend on management intensity. For example, Kitahara et al (2000) observed a highly significant decrease in butterfly species numbers with increasing mowing intensity. Likewise, Marini et al (2000) detected reduced orthopteran and butterfly diversity with high fertilisation and cutting frequency.…”
Section: Introductionmentioning
confidence: 99%